En Bloc Arch Reconstruction With the Frozen Elephant Trunk Technique for Acute Type a Aortic Dissection - Liu, Penghong; Wen, Bing; Liu, Chao; Xu, Huashan; Zhao, Guochang; Sun, Fuqiang; Zhang, Hang; Yao, Xingxing (Frontiers in Cardiovascular Medicine, 2021)
Objective: The study objective was to assess the effect of en bloc arch reconstruction with frozen elephant trunk (FET) technique for acute type A aortic dissection. Methods: From April 2018 to August 2020, 41 patients with acute Stanford type A dissection underwent en bloc arch reconstruction combined with FET implantation. The patients’ mean age was 46±13 years, and 9 patients were male. One patient had Marfan syndrome. Six patients had pericardial tamponade, 9 had pleural effusion, 5 had transient cerebral ischemic attack, and 3 had chronic kidney disease. Results: The hospital mortality rate was 9.8% (4 patients). 2 (4.9%) patients had stroke, 23 (56.1%) had acute kidney injury, and 5（12.2%）had renal failure requiring hemodialysis. During the follow-up, complete false lumen thrombosis was observed in 33 patients around the FET, in 25 patients at the diaphragmatic level, and in 10 patients at the level of the superior mesenteric artery. The true lumen diameter of all analyzed aortic segments increased while the false lumen diameter decreased at the level of the pulmonary bifurcation and the diaphragm. The actuarial 1-, 2-and 3-year survival rates were 90.2% [95% confidence interval (95% CI), 81.2-99.2], 84.2% (95% CI, 70.1-98.3) and 70.2% (95%CI, 42.2-98), respectively. Conclusions: For patients with acute type A dissection, the en bloc arch reconstruction with FET procedure appeared to be feasible and effective with early clinical follow-up results. A large sample size and long-term clinical follow-up studies are required to evaluate the efficacy.